2015
DOI: 10.1111/ped.12553
|View full text |Cite
|
Sign up to set email alerts
|

Expiratory CO2 as the first sign of successful ventilation during neonatal resuscitation

Abstract: Three-lead electrocardiography and expired CO2 monitoring were used during positive pressure ventilation of seven non-intubated newborns (gestational age, 31-37 weeks; birthweight, 1503-2885 g). In all cases, adequate CO2 (>15 mmHg) was detected prior to the achievement of stable heart rate (>100 beats/min). The delay between detection of adequate CO2 and improvement of bradycardia ranged from 8 to 73 s (median, 15 s). Inadequate expired CO2 during positive pressure ventilation indicates airway obstruction or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…ECO 2 increases rapidly in the first minute of extrauterine life during spontaneous breathing, but slower if positive pressure ventilation is needed 7–9. Capnography may help identify unfavourable technique and guide ventilations during newborn resuscitation 10–14. There is currently insufficient evidence that ECO 2 monitoring during newborn resuscitation affects outcome 3 15.…”
Section: Introductionmentioning
confidence: 99%
“…ECO 2 increases rapidly in the first minute of extrauterine life during spontaneous breathing, but slower if positive pressure ventilation is needed 7–9. Capnography may help identify unfavourable technique and guide ventilations during newborn resuscitation 10–14. There is currently insufficient evidence that ECO 2 monitoring during newborn resuscitation affects outcome 3 15.…”
Section: Introductionmentioning
confidence: 99%
“…In newborns, there were more examples of feasibility and reliability capnography monitoring during CPR. From the 13 studies in these patients (four RCT, nine observational), the vast majority considered capnometric values as a parameter for assessing the quality of ventilation (Table 2), airway patency, mask leaks, and showed a good correlation between capnography and heart rates [19,20,21,22,23,24,25,26,27,28,29,30,31]. The two RCTs that emphasized the validity of the technique were: (1) Hawkes et al, who compared the accuracy of colorimetric detector versus capnography to determine normocarbia, but they did not find a difference in the incidence of normocarbia between the two detectors.…”
Section: Resultsmentioning
confidence: 99%
“…Hooper et al [28] found EtCO 2 levels increased to >10 mmHg in 28 s (median) before the heart rate increased up to 100 bpm. Mizumoto et al [25] found an early detection of expired CO2 (>15 mmHg) between 8 and 73 s (median 15 s) before heart rate improvement. Blank et al [26] indicated that, when the EtCO 2 value was above 14 mmHg (2% in colorimetric detector), the detector showed an accuracy of 95%, detecting an increase in EtCO 2 10 to 20 s before the increase in heart rate appeared on the monitor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10À12 Results from clinical studies in mainly preterm newborns suggest that ECO 2 increases before HR during positive pressure ventilation in the delivery room. 3,13,14 Linde et al found that median ECO 2 in the first minute of bag-mask ventilation (BMV) at birth was lower in newborns who died before 24 h of age compared to survivors. 15 The aims of this study were to explore ECO 2 as a predictor of 24-h outcome (survival vs death) during newborn resuscitation with BMV, and to compare the predictive information of ECO 2 and HR.…”
Section: Introductionmentioning
confidence: 99%